Unusual presentation of patients with obsessive compulsive disorder (Bangladesh Journal of Psychiatry, 2020)
Obsessive compulsive disorder (OCD) is a common psychiatric disorder in clinical practice. But few studies have been done in Bangladesh. The aim of the study was to find out the unusual presentation of OCD patients other than common presentation. This was a cross sectional study done at private chamber and clinic in Dhaka, Bangladesh during the period of February, 2018 to January, 2019. Hundred twenty five patients fulfilling the inclusion and exclusion criteria were selected consecutively. After taking written consent a predetermined questionnaire was filled for each patient through face-to-face interview. The results showed that, most of the patients were from 21-30 years of age group (34.4%) with female preponderance (60%). Majority of the patients were married (60%), completed up to HSC level (44.8%) and students (38.4%). Among the patients the unusual presentations of OCD were new experience headache (56%), decreased sexual desire (16%), cough (9.5%), pain (8%), vomiting (8%), fit like behaviour (4%), increased frequency of micturition (2.4%) and deliberate self harm (DSH) (1.6%). The research findings will help us for the assessment, diagnosis and treatment plan. Therefore misdiagnosis and patient sufferings will be reduced.Bang J Psychiatry December 2017; 31(2): 48-50